Lesiones osteomusculares de miembros inferiores en deportistas de alto rendimiento la liga de taekwondo de Bolívar (2018)
Objective: Identify the most frequent osteomuscular injuries in high performance athletes from the Taekwondo League of Bolívar. Method: The present study is a quantitative approach of descriptive type of observational cross section, it has a population of 31 athletes who meet the inclusion criteria. Results: At the end of the investigation we can see that 45% of the population is between the ages from 18 to 23 years old; about gender we find that the masculine gender predominates in a 61%, it is important to take into account the time invested by the athletes in the training, which is from 4 to 8 hours per day in 42% of the population, this result is correlated with the activity during which the athletes said they have greater injuries and throws us a quite alarming result because most of the injuries occurred in training, with a 42%; which lead us to pay special attention to work on good practices of preventive measures to improve the performance and physical conditions of athletes. Conclusion: The specific objectives established were achieved, according to the results obtained in the study, to clearly identify the most frequent injuries in the Athletes of the Bolivar League, the most affected structures and the activity that generated most injuries, according to these results, it was recommended the use safety measures and adequate warming before and after the practice of sport, periodically body composition checks, among other measures that will help to improve overall performance of each one of them and in general of the Taekwondo League of Bolívar